Student Perception on Digital Transformation in Higher Education Institutes of Bengaluru City - Devi, K. Ambika; B. Loganayaki, B. Loganayaki (Journal of Neonatal Surgery, 2025)
Advancement of youth across the world revolves around education and hence designated as top priority by internationally recognised sustainable goals. Education sector is integral in reshaping youth’s future and providing competitive edge in global markets. Indian education industry worth 40 billion annually, with largest number of higher education institutes internationally is lucrative. As educational establishments adapt to rapidly evolving technologies, understanding students' interpretations of digital advancements is critical. With this perspective, a cross sectional survey was conducted among college going scholars ranging 18-22 years of age, to ascertain their perception towards the digitalisation in higher education institutes of Bengaluru. Questionnaire was administered to 150 randomly selected students pursuing education in Higher Education Institutes of Bengaluru. Findings indicated that though sixty-three percent of students preferred online queries about course details, only 44.7 percent of students made online inquiries. Offline inquiry were made by 33.1percent. 46 percent students rated online course information average. Though 84 percent preferred online document submissions only 65percent made online submissions. It is noteworthy document verifications for all were manual. Digital fee transactions were made by 58.7 percent while 41.3 percent used other modes of payment. Though 48.7% students sometimes had online classes, Ninety percent preferred hybrid mode for lectures. One tenth of sample reported that their colleges never used Learning management Systems (LMS). 17.3 percent of students did not prefer and 56 percent preferred LMS. Study highlighted that digitalisation has permeated in course inquiries, admission process, documentation, lectures and assessments